Information Management in New Motherhood: Does the Internet Help or Hinder?. (November 2016) - Barkin, Jennifer L.; Jani, Smit
BACKGROUND: Women are faced with the task of gathering information and making subsequent decisions for themselves and their families as they are often the primary caregivers.OBJECTIVE: The purpose of this study was to elucidate prominent themes related to information management and Internet usage in new motherhood. While the advantages to online support have been explored, triggered anxiety has not been a focus of the literature.DESIGN: A focus group study of 31 adult, postpartum women was held at a large, urban medical center in the Northeastern United States. Data related to information management were extracted and analyzed thematically.RESULTS: Women reported experiencing (a) a forcible, internal drive for information related to family health and (b) a high level of anxiety surrounding health-related Internet searches.CONCLUSIONS: Health care providers must be aware that women will consult the Internet for information and that at least a portion of those individuals will experience anxiety as a result.